Knowledge, Attitudes and Behaviors by Providing Health Education through Electronic Media (Radio) to the People of Kediri City - Ridha Rachmathiany; Riza Yuliawati (Journal for Research in Public Health, 2026)
Health education delivered through digital media, especially radio, continues to play a crucial role in the distribution of health information to the public. This study aims to examine the extent of public understanding, attitudes, and actions after receiving health education through radio in the Kediri City area. The research design applied is descriptive with quantitative methods. There were 11 respondents who were selected using purposive sampling. The tool used in this study is a questionnaire to measure knowledge, attitudes, and behaviors. The research findings showed that respondents had good knowledge of 45.45% (5 respondents), good attitudes were 90.9% (10 respondents) and sufficient behavior was 45.45% (5 respondents). So that it can show that health information broadcast via radio can be well received by the public. Meanwhile, to take action requires a process and motivation again. Health education through radio is quite effective in improving public understanding, attitudes, and actions. Radio is still considered relevant as a medium for health promotion among the community.